Comet assay: a versatile but complex tool in genotoxicity testing. Issue 1 (5th January 2021) - Cordelli, Eugenia; Bignami, Margherita; Pacchierotti, Francesca
Abstract: The comet assay is a versatile method for measuring DNA strand breaks in individual cells. It can also be applied to cells isolated from treated animals. In this review, we highlight advantages and limitations of this in vivo comet assay in a regulatory context. Modified versions of the standard protocol detect oxidized DNA bases and may be used to reveal sites of DNA base loss, DNA interstrand crosslinks, and the extent of DNA damage induced indirectly by reactive oxygen species elicited by chemical-induced oxidative stress. The assay is, however, at best semi-quantitative, and we discuss possible approaches to improving DNA damage quantitation and highlight the necessity of optimizing protocol standardization to enhance the comparability of results between laboratories. As a genotoxicity test in vivo, the in vivo comet assay has the advantage over the better established micronucleus erythrocyte test that it can be applied to any organ, including those that are specific targets of chemical carcinogens or those that are the first sites of contact of ingested or inhaled mutagens. We illustrate this by examples of its use in risk assessment for the food contaminants ochratoxin and furan. We suggest that improved quantitation is required to reveal the full potential of the comet assay and enhance its role in the battery of in vivo approaches to characterize the mechanisms of toxicity and carcinogenicity of chemicals and to aid the determination of safe human exposure limits.